Теоретичне дослідження впливу вуглецевого графеноподібного нанокластера на стабільність і міцність поліаміду у нанокомпозиті - Demianenko, E. M.; Теrets, M. I.; Sementsov, Yu. I.; Makhno, S. M.; Kuts, V. S.; Grebenyuk, A. G.; Kartel, M. T. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2019)
By the density functional theory method with the exchange-correlation functional B3LYP, the basis set 6-31G(d,p) and Grimme dispersion corrections, the energy values has been calculated of intermolecular interaction between adjacent polyamide fragments, and the effect of graphene-like nanoclusters on the similar values for intermolecular complexes of polyamide fragments with graphene-like nanoclusters has been evaluated. The effect of carbon materials on the energy magnitudes of covalent bonds in the polymer matrix of polyamide has been also examined.Comparison of the energy values of intermolecular interaction between two monomers (?86.0 kJ/mol, two hydrogen bonds) and two dimers (-302.0 kJ/mol, three hydrogen bonds) indicates that the energy of interaction between two components consists of that of hydrogen bonds and the energy contribution of dispersive forces.The energy of intermolecular interaction between two dimers with the graphene matrix (C110H26) is approximately 40 kJ/mol higher (-346.2 kJ/mol) compared to respective value for two monomers. The less value of the interaction energy (-325.0  kJ/mol) for the nanocomposite with C96H24 species is due to the insufficient size of the selected model for the graphene matrix.The analysis of the hydrogen bond lengths between the oxygen atom of carbonyl group and hydrogen one of amino group indicates that, regardless of length of linkage of the polymeric chain of polyamide (monomer and dimer) and the size of the graphene-like matrix (C96H24 and C110H26) in the nanocomposite, the hydrogen bond in composites is shorter in comparison with a those values in complexes without a carbon matrix. This indicates a greater strength of the bond, that is, the presence of a carbon matrix increases the strength of the formed nanocomposite, that explains the increase in the melting point compared with that of the original polymer. In the nanocomposite formed polyamide - a carbon matrix for all the models studied, the energy of intermolecular interaction in the nanocomposite increases significantly compared to respective value between two fragments of pure polyamide, so indicating an increase in the thermal stability of this nanocomposite what is confirmed by experimental data.